2005
DOI: 10.1037/0097-7403.31.1.107
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective Revaluation as Simple Associative Learning.

Abstract: Backward blocking, unovershadowing, and backward conditioned inhibition are examples of retrospective revaluation phenomena that have been suggested to involve more than simple associative learning. Models of these phenomena have thus used additional concepts, for example, appealing to attentional effects or more elaborate learning mechanisms. The author shows that a suitable representation of stimuli, paired with a careful analysis of the discriminations faced by animals, leads to an account of these and othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 33 publications
0
29
0
Order By: Relevance
“…Minerva-AL's explanation of retrospective revaluation as de novo learning via within-compound associations is consistent with a number of other models (e.g., Dickinson & Burke, 1996;Ghirlanda, 2005;Miller & Matzel, 1988;Van Hamme & Wasserman, 1994;Witnauer & Miller, 2011). However, Minerva-AL offers a unique computational description of how that process unfolds by a combination of discrepancy encoding and trace inversion at retrieval.…”
Section: Section 5: Retrospective Revaluationmentioning
confidence: 75%
“…Minerva-AL's explanation of retrospective revaluation as de novo learning via within-compound associations is consistent with a number of other models (e.g., Dickinson & Burke, 1996;Ghirlanda, 2005;Miller & Matzel, 1988;Van Hamme & Wasserman, 1994;Witnauer & Miller, 2011). However, Minerva-AL offers a unique computational description of how that process unfolds by a combination of discrepancy encoding and trace inversion at retrieval.…”
Section: Section 5: Retrospective Revaluationmentioning
confidence: 75%
“…The Rescorla-Wagner model handily accounts for blocking, but because it assumes absent cues have zero influence on learning, it cannot account for backward blocking. Extensions of the model, that assume absent cues have a negative impact on learning, can account for backward blocking or other effects (Dickinson & Burke, 1996;Ghirlanda, 2005;Markman, 1989;Tassoni, 1995;Van Hamme & Wasserman, 1994). The models assert that only absent cues that are expected to be present should have negative impact, but the exact computations regarding which cues are expected, and their magnitude of negativity, have been left unspecified.…”
Section: Application To Blocking and Backward Blockingmentioning
confidence: 99%
“…Furthermore, the importance or strength of correct (β 1 ) vs. incorrect (β 2 ) predictions can be weighted differentially. Although in a typical simulation run these parameters are set to their default values, they allow for a principled account of various learning ÒpeculiaritiesÓ (see Ghirlanda, 2005 for how a simple error-driven learning model, formally equivalent to the Rescorla-Wagner model, can account for a range of intricate learning phenomena). For example, in a series of experiments and modelling studies it was shown that a change in the salience of a crucial learning cue could explain an unexpected pattern of results in a variant of the object naming task, designed to demonstrate the highlighting effect in learning.…”
Section: Learning Theorymentioning
confidence: 99%